Analisis Indeks Beban Kerja dan Daftar Susunan Personel dalam Rangka Validasi guna Mewujudkan Organisasi TNI Angkatan Laut yang Adaptif - Yudistira, Henky Irawan; Fartianto, Gurtom; Achnaf, Mochamad (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
A human resource management system can help in tracking and analyzing workloads in real-time and provide better insights for workforce planning. Advanced analytics tools can be used to predict future workforce needs and adjust the number of personnel according to existing trends and work patterns. The purpose of this study is to find out and analyze how the calculation of the Workload Index will be used for validation, To find out and analyze how to prepare the recommended Personnel Composition List in the implementation of organizational validation, To find out and analyze how the organizational validation process works. In this study, the researcher used a qualitative method with a descriptive analysis approach. Qualitative research methods are a method or research method that emphasizes more analysis or descriptiveness. Research activities are carried out in Srenaal and Spersal with the research instrument being the researcher himself, which means that the researcher himself makes observations and takes research data. The sample of data sources used by the researcher used purposive sampling. The conclusion of the results of this study is that the Task Force Workload Index Calculation must be filled by each Navy personnel according to their position space, but in the field there are many personnel who are BKO, Based on the results of interviews with seven informants, it shows that the list of personnel composition there is no coordination between the task force that proposes validation and the Spersal Ban II, the determination of the number of willing personnel on the basis of the Satkel that proposes validation, The determination of the number of personnel is not studied first using IBK. Organizational Validation has not adhered to the concept of Poor Structure Rich Function. The Task Force does not yet understand the organizational validation mechanism.